Analysis of related factors of clinical and renal pathological characteristics in patients with idiopathic membranous nephropathy - GUO Guang-feng; XIE Da-xing; ZHANG Xue-qin; REN Hui-min; LU Chen (Linchuang shenzangbing zazhi)
Objective To study the clinical and pathological characteristics of idiopathic membranous nephropathy（IMN） and their influence on glomerular filtration rate. Methods A total of 119 patients with IMN diagnosed in Xinjiang Uygur Autonomous Region People’s Hospital from January 2017 to December 2018 were enrolled. According to the estimated glomerular filtration rate（eGFR）, the patients were divided into normal renal function group[58 cases, eGFR≥90 mL·min-1·（1.73 m2）-1]and declined renal function group[61 cases, eGFR<90 mL·min-1·（1.73 m2）-1]. The general data, clinical and pathological data of the patients were compared and analyzed. Results With respect to clinical data, the age, hypertension patient proportion, serum creatinine and urea nitrogen of the patients in the declined renal function group（declined eGFR） were significantly higher than those in the normal group（P<0.05）, and the serum albumin and serum total protein levels were significantly lower than those in the normal group（P<0.05）. With respect to real pathology,the rates of glomerulosclerosis, tubular atrophy, renal interstitial fibrosis, interstitial inflammatory cell infiltration and thickened small arteryin the declined renal function group were significantly higher than those in the normal renal function group（P<0.05）. Logistic regression analysis showed that age, serum albumin level and renal interstitial inflammatory cell infiltration were independent risk factors for declined eGFR in IMN patients; and increased serum albumin level was a protective factor of declined eGFR. Conclusions For IMN patients, the renal function should be improved by improving the level of serum albumin and controlling the infiltration of renal interstitial inflammatory cells, so as to delay the progression of the disease.